2022
DOI: 10.1111/jsr.13581
|View full text |Cite
|
Sign up to set email alerts
|

Novel oxygen desaturation parameters are associated with cardiac troponin I: Data from the Akershus Sleep Apnea Project

Abstract: Novel diagnostic markers for obstructive sleep apnea beyond the apnea-hypopnea index (AHI) have been introduced. There are no studies on their association with markers of subclinical myocardial injury. We assessed the association between novel desaturation parameters and elevated cardiac troponin I and T. Participants with polysomnography (498) from the Akershus Sleep Apnea study were divided into normal and elevated biomarker groups based on sex-specific concentration thresholds (cardiac troponin I: ≥4 ng/L f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Other studies finding associations between metrics incorporating oxygen desaturation curve area and CVD outcomes or mortality have used a full spectrum of data from no disease to severe OSA [ 13 , 14 ]. In terms of the potential advantage of more novel oxygen desaturation assessments compared to AHI another recent study has looked at this using the outcome of subclinical myocardial injury (cardiac troponin levels) [ 40 ]. This study found AHI, ODI, and novel metrics (incorporating oxygen desaturation area) were all similarly useful, with no advantage of the novel metrics, in discriminating those with elevated troponin [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies finding associations between metrics incorporating oxygen desaturation curve area and CVD outcomes or mortality have used a full spectrum of data from no disease to severe OSA [ 13 , 14 ]. In terms of the potential advantage of more novel oxygen desaturation assessments compared to AHI another recent study has looked at this using the outcome of subclinical myocardial injury (cardiac troponin levels) [ 40 ]. This study found AHI, ODI, and novel metrics (incorporating oxygen desaturation area) were all similarly useful, with no advantage of the novel metrics, in discriminating those with elevated troponin [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the potential advantage of more novel oxygen desaturation assessments compared to AHI another recent study has looked at this using the outcome of subclinical myocardial injury (cardiac troponin levels) [ 40 ]. This study found AHI, ODI, and novel metrics (incorporating oxygen desaturation area) were all similarly useful, with no advantage of the novel metrics, in discriminating those with elevated troponin [ 40 ]. A large OSA clinical cohort has found similar associations among ODI, T90, and “hypoxic burden” metrics in predicting major adverse CV events or all-cause mortality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several markers to measure hypoxaemic burden during sleep, including minimal saturation (MinSatO 2 ), the oxygen desaturation index (ODI), TST90%, sleep-apnoea-specific hypoxic burden (measured as the area under the desaturation curve associated with respiratory events) [ 23 , 24 ], desaturation duration (the cumulative time of desaturations) and desaturation severity (the sum of the areas of all desaturation events) [ 25 , 26 ]. Whilst the former three are readily available on sleep reports, the latter three need to be calculated with external software.…”
Section: Introductionmentioning
confidence: 99%
“…There are several markers to measure hypoxaemic burden during sleep, including minimal saturation (MinSatO 2 ), the oxygen desaturation index (ODI), TST90%, sleep apnoea-speci c hypoxic burden (measured by the area under the desaturation curve associated with respiratory events) [22,23], desaturation duration (the cumulative time of desaturations) and desaturation severity (the sum of the areas of all desaturation events) [24,25]. Whilst the former three are readily available on sleep reports, the latter three need to be calculated with an external software.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the former three are readily available on sleep reports, the latter three need to be calculated with an external software. The merit of the latter indices is that they take into account both the depth and duration of desaturation; however, their additive value compared to TST90% is limited [22,24]; but might outperform TST90% in selected populations [22]. Time spent with saturation below 80% (TST80%) is a metric which is also often readily provided by the sleep studies and does not require further transformation.…”
Section: Introductionmentioning
confidence: 99%